Percutaneous catheter decompression in a neonate with multiple small bowel atresias - Lana Bricknell; Roy M. Kimble (Elsevier, 2021)
The management of infants with multiple intestinal atresia and complex gastroschisis can represent a challenge to the paediatric surgeon. This case report presents a neonate with multiple jejunal atresias in which a percutaneous foley catheter tube inserted to just beyond the duodenojejunal flexure was used effectively for bowel decompression, instead of the formation of a proximal stoma. By utilising this technique, the well documented complications associated with proximal stomas were avoided, bowel length was preserved and the need for further surgery in the infant was prevented. The infant remained well at six months with no complications at follow-up.